A Mini Review on Risk and Potential of Biogas Fed Solid Oxide Fuel Cell - Lim, Bee Huah; Masli Irwan, Rosli; Lim, Soh Fong (UKM Press (Universiti Kebangsaan Malaysia Publisher)., 2023)
Solid oxide fuel cell (SOFC) can reduce the carbon footprint due to their flexibility of fuel usage by using hydrogen and light hydrocarbon as fuel to convert the chemical to electrical energy. This has made the SOFC an interesting device for renewable applications. SOFC which is able to convert the biogas produces from the water treatment plant directly to electrical energy is a reliable renewable energy application. The performance of SOFC itself can be greatly influenced by the characteristics of the biogas. This is caused by the impurities of the biogas that would degrade the internal reforming aspect of SOFC. Mainly on the anode side degradation due to the formation of carbon, sulfur poisoning, and mechanical instability. The commonly found biogas impurities from the wastewater treatment plant are Siloxanes. The compound is coming from sewage sludge digestion which is the common compound in household cleaning products and cosmetics. The presence of Siloxanes in internal reforming SOFC would lead to the formation of SiO2 which degrade the anode layer and consequently reduces the power generation of SOFC. Hydrogen sulfide and ammonia were also present in the biogas fed from the wastewater treatment plant. These contaminations also showed degradation in the SOFC of the anode. Thus, this work will discuss the contamination compound and its effect on SOFC.